Respostas

2013-04-29T20:50:53-03:00

se f(x)=ax+b, f(1)=4 e f(2)=7...

logo temos um simples sistema com f(1) e f(2):

{a*1+b=4

{a*2+b=7

invertemos um deles para negativo...

(-1)* {-a -b= -4

         {2a+b= 7

           a = 3...

logo a + b = 4

           b = 4 - 3

              b = 1

então...

f(8)= 3*8+1

f(8) = 24+1

f(8) = 25

2 5 2
2013-04-29T21:04:50-03:00

 f(2)=  ax + b = 7 -->    2a + b = 7  . ( -1 )  --->   -2a -b = -7

 f(1)=  ax + b = 4 --->     a + b = 4  ------------->      a+b = 4

                                                                                _________

                                                                                  -a     = -3  ----> a = 3

 

 

                                             Se  a + b = 4 --->  b = 4 - a ---->  b = 4 - 3  ---> b = 1

 

 

          f(8) = 8a + b = 8 . 3 + 1   --->  f(8) = 24 + 1 ----->  f(8) = 25